Online content risk among adolescents: reviews on Malaysia law and policy / Siti Elda Nadzirah Rosli, Wardatul Hayat Adnan and Ahlam Abdul Aziz - Rosli, Siti Elda Nadzirah; Adnan, Wardatul Hayat; Abdul Aziz, Ahlam (Centre For Media And Information Warfare Studies, 2021)
Content risk protection is an important problem that must be investigated further. This is owing to the upsetting consequences that uncontrollable content circulated among the public, particularly through online media. The public's embrace and use of online media has increased the complexity of controlling this issue. The ease of accessibility is also one of the reasons why so many people use this media. Furthermore, research has shown that online content has a considerable potential for influencing and affecting adolescents. Tighter regulation and enforcement, as well as education and knowledge about risk protection in relation to online content, are all necessary safeguards. The purpose of this study is to review the available research on internet content risk protection for adolescents, as well as the laws and policies in place to address these issues. In order to gather information about the topic, a keyword search was employed. In addition, articles were also grouped the effects of online content towards adolescents in the context of learning, participation, creativity and identity. This has helped to oversee online content risk protection towards Malaysia Adolescents status in compared to others. In conclusion, the results of the review have its potential in assisting readers to understand the policy and regulations available to protect adolescents in Malaysia in the context of online content.